ALKBH4 Functions as a Suppressor of Colorectal Cancer Metastasis via Competitively Binding to WDR5 - Shen, Chaoqin; Yan, Tingting; Tong, Tianying; Shi, Debin; Ren, Linlin; Zhang, Youwei; Zhang, Xinyu; Cao, Yingying; Yan, Yuqing; Ma, Yanru; Zhu, Xiaoqiang; Tian, Xianglong; et al. (Frontiers in Cell and Developmental Biology, 2020)
Background: Epithelial-Mesenchymal Transition (EMT) is a major process in the initiation of tumor metastasis, where cancer cells lose sessile epithelial potential and gain mesenchymal phenotype. Large-scale cell identity shifts are often orchestrated on an epigenetic level and the interplay between epigenetic factors and EMT progression was still largely unknown. In this study, we tried to identify candidate epigenetic factors that involved in EMT progression. Methods: Colorectal cancer (CRC) cells were transfected with an arrayed shRNA library targeting 384 genes involved in epigenetic modification. Candidate genes were identified by real-time PCR. Western blot, RNA-seq and gene set enrichment analysis (GSEA) were conducted to confirm the suppressive role of ALKBH4 in EMT. The clinical relevance of ALKBH4 in CRC was investigated in two independent Renji Cohorts and a microarray dataset (GSE21510) from GEO database. In vitro transwell assay and in vivo metastatic tumor model were performed to explore the biological function of ALKBH4 in the metastasis of CRC. CO-IP (Co-Immunoprecipitation) and ChIP (Chromatin Immunoprecipitation) assays were employed to uncover the mechanism. Results: We screened for candidate epigenetic factors that affected EMT process and identified ALKBH4 as a candidate EMT suppressor gene, which was significantly downregulated in CRC patients. Decreased level of ALKBH4 was associated with metastasis and predicted poor prognosis of CRC patients. Follow-up functional experiments illustrated overexpression of ALKBH4 inhibited the invasion ability of CRC cells in vitro, as well as their metastatic capability in vivo. Mechanistically, CO-IP and ChIP assays indicated that ALKBH4 competitively bound WDR5 (a key component of histone methyltransferase complex) and decreased H3K4me3 histone modification on the target genes including MIR21. Conclusions: This study illustrated that ALKBH4 may function as a novel metastasis suppressor of CRC, and inhibits H3K4me3 modification through binding WDR5 during EMT.